The Nexus between Mentoring Dimensions and Organizational Commitment of Academic Staff in Selected Private Universities in South-West Nigeria (Global Journal of Management and Business Research, 2019)
Effective mentorship aids employee retention by enhancing organisational commitment. Using the responses of 315 academic staff and in-depth interviews of professors and junior lecturers of six selected private universities in South-West Nigeria, this study explored mentoring as an emerging form of leadership development programs and its concomitant relationship with employee outcomes with a view to making veritable recommendations for its adoption to build skills and human capacity in Nigerian universities. Despite the various forms of mentoring, it focused on workplace/organisational mentoring. The two main types of mentoring discussed were formal and informal mentoring. Correlation analysis was used to analyse the hypothesis which was supported. Findings revealed that mentoring dimensions had a significant weak positive relationship with employee commitment (r=0.121, 0.150, 0.159, 0.188, 0.203, plt; 0.05, N=315). The qualitative findings indicated that mentoring to a large extent positively affects employees#x2019; organisational commitment. Finally, implications for future research were mentioned. While mentoring relationships have a positive impact on each of the dimensions of commitment, affective commitment is most influenced. It was recommended that every university should put in place structures that would support mentoring and align it with faculty#x2019;s promotion.
Keywords: employees#x2019; behavioural outcomes; mentoring; nigeria; organisational commitment; retention